Construction of graphene network in Ni matrix composites: A molecular dynamics study of densification process. (May 2022) - Yang, Yanjie; Liu, Mabao; Du, Jianxun; Zhang, Wei; Zhou, Shiqi; Ren, Weijia; Zhou, Qihang; Shi, Lan
Abstract: Graphene network (GN) reinforced metal matrix composites have been proved to possess a combination of high strength and good ductility, but the formation mechanism of GN, which serves as the source of excellent mechanical properties, is rarely revealed. In this study, the construction of network architecture in graphene network reinforced Ni matrix composites (GN/Ni) is investigated by molecular dynamics (MD). Results show that discrete graphene sheets covered on Ni particles are assembled into an intact and continuous graphene network through interlayer and lateral connections. The curvature of GN walls caused by defects, together with the corners of GN near the intersections of multi Ni particles, realizes the 3D network architecture composed of nondevelopable surfaces. The GN intertwines intimately with the Ni matrix to construct an interlocking structure, where a robust interface is induced by the strong Ni–C interactions and the redistribution of internal stress. Besides, owing to the restricted atomic motion of Ni matrix by GN during densification, dislocation accumulation near the GN is actualized in GN/Ni, as well as the grain refinement. This work can benefit the optimization of graphene reinforced metal matrix composites for fulfilling the strengthening and toughening potentials of GN. Graphical abstract: Image 1